Academic Leaders’ Experiences of Inclusive Education through the Lens of Positive Psychology - Jason V. Chavez; Rolly G. Salvaleon; Maria Lady Sol A. Suazo; Abundio C. Miralles; Maria Cristina S. Dela Cerna; Sitti Khadija M. Dammang; Nuryneil M. Joe; Cindy May P. Tacbobo; Kier P. Dela Calzada (Journal of Qualitative Research in Education, 2026)
This study explored how academic leaders applied principles of positive psychology in fostering inclusive educational environments and examined how positive psychological traits shaped their leadership experiences, challenges, and strategies. Anchored in an exploratory qualitative research design, the study sought to capture the lived experiences and leadership practices of academic leaders within diverse institutional contexts. One-on-one semi-structured interviews were conducted with eighteen (18) academic leaders, allowing for in-depth insights into how inclusion was enacted beyond formal policies. The collected data were analyzed using reflexive thematic analysis to identify recurring patterns and meanings across participants’ narratives. Findings revealed that academic leaders operationalized positive psychology through hope-oriented practices, well-being initiatives, strengths-based leadership approaches, and the intentional cultivation of belongingness within their institutions. These practices played a significant role in nurturing inclusive cultures by promoting psychological safety, collaboration, mutual respect, and active engagement among both students and staff. Moreover, the results highlighted that positive psychological traits, particularly resilience, optimism, empathy, and gratitude, served as essential leadership resources. These traits enabled leaders to navigate institutional constraints, sustain inclusive initiatives over time, and respond adaptively to resistance, change, and learner diversity. The study concluded that inclusive education was strengthened not solely through policies, frameworks, or structural mechanisms, but through everyday leadership practices grounded in positive psychological principles. Embodying and modeling these traits, academic leaders translated inclusive ideals into meaningful institutional practice. The study concluded that inclusive education was strengthened not only through policies and structural mechanisms but through leadership practices grounded in positive psychological principles, underscoring the central role of academic leaders in translating inclusion from policy intent into institutional practice.